Awareness of institutional repository contents for academic productivity by faculty members in Federal University, Dutsin-Ma, Katsina State – Nigeria - Abdul, Sherifat; Umar, Babangida Dangani; Abba, Hamza (Communicate: Journal of Library and Information Science, 2025)
This study examined the awareness of Institutional Repository Contents for Academic Productivity by Faculty Members in Federal University Dutsin-ma, Katsina State, Nigeria, in order to achieve this, two (2) objectives of the study were formulated. Quantitative research methodology was adopted and cross-sectional survey research design was used for the study. The population of this study comprised of all the one thousand four hundred and sixteen (1,416) academic staff of Federal University Dutsin-ma (FUDMA). Three hundred and nine (309) academic staff were used as a sample size using Krejcie and Morgan sample size determination Table. Self-developed questionnaire was used to collect data from the respondents. Descriptive statistics was used to present and analyse the data. The study found that, theses, dissertations, journal article, conference papers/proceedings, books, book chapters, seminar papers, creative works and educational resources (course materials and educational videos) were the Institutional Repository Contents with the high level of awareness among academic staff in FUDMA; it was also found that; increased visibility and accessibility of research outputs, long term preservation and archiving platform, global outreach and collaboration/knowledge sharing, efficient management of Institutional knowledge, and encourage qualitative outputs were the main benefits derived from utilizing Institutional Repository by faculty members of FUDMA. The study concluded that enhancing awareness of institutional repository contents is crucial for boosting academic productivity among faculty members at Federal University, Dutsin-Ma, Katsina State, Nigeria and recommended that; the Federal University Dutsin-ma (FUDMA) Library should engage in aggressive awareness campaign to promote the use of IR in the university.